Paleoclimatic and paleoenvironmental constraints on organic matter enrichment in the Paleocene strata in the Lishui Sag, East China Sea Shelf Basin - Shiyan Yin; Chuang Lei; Jiaren Ye; Jingfu Wu; Yu Wang; Ying Zhang; Xiaoying Han (Energy Geoscience, 2025)
Using major and trace element analyses, this study investigated the impacts of paleoclimatic and paleoenvironmental variations on organic matter enrichment in the Paleocene Yueguifeng, Lingfeng, and Mingyuefeng formations in the Lishui Sag, East China Sea Shelf Basin. Multiple geochemical proxies suggest that during the deposition of the three formations, the paleoclimate evolved from a humid climate to an arid and then back to humid conditions, the paleosalinity conditions underwent brackish, saline, and fresh water sequentially, and the paleowater conditions shifted from relatively deep water to relatively shallow water and then to shallow water. Accordingly, the water column evolved from reducing to oxidizing and then to weakly oxidizing to oxidizing conditions. Organic matter productivity, as well as the preservation or degradation of organic matter, was controlled by covariation in the paleoclimatic and paleoenvironmental conditions. This can account for the difference in organic matter enrichment in the mudstones of the three formations. The mudstones in the Yueguifeng Formation were deposited in a semi-deep- to deep-water lacustrine environment with high primary productivity in a warm, humid climate. Numerous planktonic algae were efficiently preserved in stratified and dysoxic water columns, resulting in high organic matter enrichment in this formation. The mudstones in the Lingfeng Formation were formed in a shallow marine environment with low primary productivity in an arid climate. The combined effects of high salinity and oxygen-enriched conditions in the water bodies were unfavorable for the reproduction and preservation of planktonic algae, resulting in low organic matter enrichment. For the Mingyuefeng Formation, the slow tectonic subsidence and flat topography during the deposition of this formation led to the development of a swamp environment in a warm, humid climate. The swamp environment was characterized by an oxic water column, low aquatic organic matter input, and high terrigenous organic matter input. The Yueguifeng Formation has greater hydrocarbon-generating potential than the Lingfeng and Mingyuefeng formations. Constructing the developmental models of organic-rich mudstones based on the covariation in the paleoclimatic and paleoenvironmental conditions represents a valid method for understanding the hydrocarbon-generating potential of these source rocks.